Ketamine treatment for individuals with treatment-resistant depression: Longitudinal qualitative interview study of patient experiences - Lascelles, K; Marzano, L; Brand, F; Trueman, H; McShane, R; Hawton, K (Cambridge University Press, 2020)
Background: Ketamine has recently received considerable attention regarding its antidepressant and anti-suicidal effects. Trials have generally focused on short-term effects of single intravenous infusions. Research on patient experiences is lacking.